Analisis Pelayanan Maskapai Penerbangan PT “X” Rute Jakarta-Batam Berdasarkan Persepsi Penumpang - Sitti Subekti (Research and Development Agency of The Ministry of Transportation, 2013)
The complexity of competition in the air transport industry causing any company or airlines have to improve the quality of service to the customer. This study uses the variable consists of 23 attributes of services that includes 5 SERVQUAL dimensions namely reliability, responsiveness , empathy , assurance and tangibles . Importance Performance Analysis Methods and Customer Satisfaction Index is used to analyze the primary data . The results showed that there are three (3 ) service attributes that are in quadrant priorities for improved / enhanced service which are ( A4 ) on-time performance of airline service, (Re5) ease of reservation and ( Rs3 ) ease of buying a ticket and check -in service at the airport . Customer Satisfaction Index of PT